2021
DOI: 10.4103/ijpc.ijpc_64_21
|View full text |Cite
|
Sign up to set email alerts
|

End of life care in end-stage kidney disease

Abstract: There is a rise in burden of end-stage renal disease globally and in India. The symptom burden, prognosis, and mortality in chronic kidney disease closely mimics that of cancer. However, the palliative and end of life care needs of these patients are seldom addressed. A consensus opinion statement was developed outlining the provision of end of life care in end-stage kidney disease. Recognition of medical futility, consensus on medical futility, and cessation of potentially inappropriate therapies and medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…Several other studies also report that terminally-ill patients from non-cancer diseases approaching EOL suffer comparably high burdens of disease similar to those dying from advanced cancer (Gore et al, 2000; Lastrucci et al, 2018; Mizuno et al, 2021; Murray et al, 2002; Prabhu et al, 2021; K. Roth et al, 2000).…”
Section: Comparison Of Eol Signs and Symptoms In Cancer Versus Non-ca...mentioning
confidence: 95%
See 1 more Smart Citation
“…Several other studies also report that terminally-ill patients from non-cancer diseases approaching EOL suffer comparably high burdens of disease similar to those dying from advanced cancer (Gore et al, 2000; Lastrucci et al, 2018; Mizuno et al, 2021; Murray et al, 2002; Prabhu et al, 2021; K. Roth et al, 2000).…”
Section: Comparison Of Eol Signs and Symptoms In Cancer Versus Non-ca...mentioning
confidence: 95%
“…Likewise, a large-scale systematic review analysis of 64 original studies that compared symptom prevalence in people with markedly advanced cancer, AIDS, heart disease, chronic pulmonary disease, and renal disease concluded that the common pathway toward death is similar for both cancerous and non-cancerous diseases (Solano et al, 2006). Several other studies also report that terminally-ill patients from non-cancer diseases approaching EOL suffer comparably high burdens of disease similar to those dying from advanced cancer (Gore et al, 2000;Lastrucci et al, 2018;Mizuno et al, 2021;Murray et al, 2002;Prabhu et al, 2021;K. Roth et al, 2000).…”
Section: Comparison Of Eol Signs and Symptoms In Cancer Versus Noncan...mentioning
confidence: 99%
“…Kidney failure is a global health issue that affects the minority and low-income communities. Based on data from the WHO Global Burden of Disease (GBD) it is stated that 5-10 million people die each year due to kidney disease [1]. The prevalence rate of kidney failure in Taiwan is the highest in the world due to a longer life expectancy while the population continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, sabe-se que o oxigênio é útil e traz benefício apenas quando há presença de hipoxemia. Estratégias de manejo não farmacológico, como manter o quarto arejado e fluxo de vento focado no rosto, podem melhorar a sensação de falta de ar (PRABHU et al, 2021).…”
Section: Discussionunclassified